Enhancing betalains production and antioxidant activity in Celosia argentea cell suspension cultures using biotic and abiotic elicitors - Kanchanok Mueangnak; Haruthairat Kitwetcharoen; Sudarat Thanonkeo; Preekamol Klanrit; Jirawan Apiraksakorn; Poramaporn Klanrit; Poramate Klanrit; Pornthap Thanonkeo (Scientific Reports)
Abstract Celosia argentea is a plant known for producing bioactive compounds, including betalains, which possess various biological and pharmaceutical properties. This study aimed to investigate the effect of biotic and abiotic elicitors on betalains production and their antioxidant activity in cell suspension cultures of C. argentea. Various concentrations of chitosan, yeast extract, salicylic acid, methyl jasmonate, copper sulfate (CuSO4), and cobalt chloride (CoCl2) were evaluated. The results revealed that chitosan, salicylic acid, methyl jasmonate, and CuSO4 significantly improved betalains production in the cell suspension cultures. Among these elicitors, chitosan at 5.0 mg/L and CuSO4 at 6.4 µM were the most effective in enhancing betalains production, yielding the highest concentrations of 4.65 and 4.99 mg/g dry weight, respectively. Notably, the betalains derived from the elicitor-treated cultures exhibited greater antioxidant activity compared to the control. These findings suggest that chitosan and CuSO4 are promising elicitors for sustainable in vitro production of betalains from C. argentea cell suspension cultures on a commercial scale, owing to their ability to enhance betalains production and antioxidant activity.